Social engineering : the science of human hacking - Hadnagy, Christopher (John Wiley & Sons, Inc., 2018)
Harden the human firewall against the most current threats Social Engineering: The Science of Human Hacking reveals the craftier side of the hacker's repertoire--why hack into something when you could just ask for access? Undetectable by firewalls and antivirus software, social engineering relies on human fault to gain access to sensitive spaces; in this book, renowned expert Christopher Hadnagy explains the most commonly-used techniques that fool even the most robust security personnel, and shows you how these techniques have been used in the past. The way that we make decisions as humans affects everything from our emotions to our security. Hackers, since the beginning of time, have figured out ways to exploit that decision making process and get you to take an action not in your best interest. This new Second Edition has been updated with the most current methods used by sharing stories, examples, and scientific study behind how those decisions are exploited. Networks and systems can be hacked, but they can also be protected; when the "system" in question is a human being, there is no software to fall back on, no hardware upgrade, no code that can lock information down indefinitely. Human nature and emotion is the secret weapon of the malicious social engineering, and this book shows you how to recognize, predict, and prevent this type of manipulation by taking you inside the social engineer's bag of tricks